A longitudinal study of the effects of discrimination on the acculturation strategies of international students - Ramos, M. R. (2017)
The current study investigated the impact of discrimination on the acculturation strategies of international students in the United Kingdom. In a longitudinal study that followed students (N = 113) for 1 year, the authors drew on social identity theory to understand the processes by which discrimination affects their acculturation strategies. Specifically, the study examined an indirect effect by which perceived discrimination affects acculturation strategies through perceived permeability of group boundaries. Results showed that perceiving discrimination is associated with a perceived lack of permeability, which in turn results in avoiding the host society and simultaneously endorsing one's own cultural background. Implications for international students and other cultural groups are discussed.